Genetic Screening for Arabidopsis Mutants Defective in STA1 Regulation under Thermal Stress Implicates the Existence of Regulators of Its Specific Expression, and the Genetic Interactions in the Stress Signaling Pathways - Yu, Si-in; Han, Jin-Hee; Chhoeun, Chanvotey; Lee, Byeong-ha (Frontiers in Plant Science, 2016)
To cope with environmental stresses, plants have developed various stress tolerance mechanisms that involve the induction of many stress responsive genes through stress-specific and common signaling pathways. Stress-specific/common transcription factors, rather than general basal factors, were considered important in this stress tolerance. The Arabidopsis STABILIZED1 (STA1) gene encodes a putative pre-mRNA splicing factor that is similar to the human U5 snRNP-associated 102-kDa protein and the yeast pre-mRNA splicing factors, PRP1p and Prp6p. As pre-mRNA splicing is a necessary process for proper gene expression in eukaryotes, STA1 is expected to be constantly functional in all conditions. Interestingly, STA1 expression is induced by temperature stresses, and STA1 recessive mutation (sta1-1) resulted in temperature stress-specific hypersensitivity. This suggests STA1’s stress specific function in addition to its presumed “housekeeping” role. In order to establish the genetic system to understand the regulation of STA1 expression in temperature stresses, we generated a bioluminescent Arabidopsis plant harboring the STA1 promoter fused to the firefly luciferase coding sequence (STA1p-LUC). Through genetic analysis, the bioluminescent Arabidopsis homozygous for one-copy STA1p-LUC was isolated and characterized. In this STA1p-LUC line, the expression patterns of STA1p-LUC were similar to those of the endogenous STA1 gene under cold and heat stresses. The STA1p-LUC line was then chemically mutagenized and screened to isolate the genetic loci of STA1 regulators under cold or heat stresses. Mutants with altered STA1p-LUC luminescence were identified and further confirmed through luminescence imaging in the next generation and analysis of endogenous STA1 expression. The categorization of STA1p-LUC deregulated mutants implicated the existence of cold or heat stress-specific as well as common genetic regulators for STA1 expression. Interestingly, some mutants showed opposite-directional deregulation of STA1 expression depending on the type of thermal stress, suggesting that the loci may represent important switch factors which determine the direction of signaling pathways for STA1 expression in response to temperature.